Key to the species of Eotrechinae (Hemiptera: Heteroptera: Gerridae) of Thailand and review of the fauna of the Phetchabun Mountain Range - Nakthong, La-Au; Vitheepradit, Akekawat; Sites, Robert W. (Zootaxa, 2014)
Water striders of the subfamily Eotrechinae from the Phetchabun Mountain Range can be found at the margins of rock pools and puddles, and in hygropetric habitats including waterfalls. Twenty-two species in three genera are known from Thailand. In the Phetchabun Mountain Range, 12 species representing all three genera were recorded from over a decade of collections (2002–2012). This paper provides taxonomic, biological, and ecological information for taxa of the Phetchabun Mountain Range in Thailand and a taxonomic key to all known species from Thailand.